2010
DOI: 10.1016/j.jcin.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Role of Remote Ischemic Periconditioning in Primary Percutaneous Coronary Intervention

Abstract: These findings demonstrate a cardioprotective effect of RIPC and morphine during primary percutaneous coronary intervention for the prevention of reperfusion injury. This is in agreement with observations that the beneficial effect of RIPC is inhibited by the opioid receptor blocker naloxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(163 citation statements)
references
References 26 publications
6
154
2
1
Order By: Relevance
“…A metaanalysis including 244 patients treated by PPCI suggested that preconditioning resulted in lower mean peak creatine kinase release, and improved left ventricular ejection fraction and myocardial reperfusion, compared with controls. 44 Interestingly, Rentoukas et al 45 showed that the beneficial effect of remote IPC on ST-segment resolution in patients treated by PPCI was increased by the concomitant administration of morphine. Remote preconditioning is unique in that it can be applied during myocardial ischaemia, prior to reperfusion.…”
Section: Prevention and Treatment Of Ischaemia-reperfusion Injurymentioning
confidence: 99%
“…A metaanalysis including 244 patients treated by PPCI suggested that preconditioning resulted in lower mean peak creatine kinase release, and improved left ventricular ejection fraction and myocardial reperfusion, compared with controls. 44 Interestingly, Rentoukas et al 45 showed that the beneficial effect of remote IPC on ST-segment resolution in patients treated by PPCI was increased by the concomitant administration of morphine. Remote preconditioning is unique in that it can be applied during myocardial ischaemia, prior to reperfusion.…”
Section: Prevention and Treatment Of Ischaemia-reperfusion Injurymentioning
confidence: 99%
“…Primary PCI is the gold standard, and the first study to examine RIC in this setting included 33 patients in each group, but was negative 95. Interestingly, in this study, while RIC did not provide additional benefit over the control group, a third group that received morphine in addition to RIC had less myocardial injury, suggesting a synergistic role for RIC with an opioid.…”
Section: Ric In Stemi Patients Treated By Primary Pcimentioning
confidence: 76%
“…In recent decades, IR injury has become a topic of particular interest in the context of liver surgery and research. Studies have predominantly focused on RIPC, which is a strategy for harnessing the body's endogenous protective capabilities against the injury that is incurred during IR (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). NO is an essential mediator of the protection that is afforded by hind-limb RIPC against liver IR injury (25).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that remote ischemic preconditioning (RIPC) represents a strategy for harnessing the body's endogenous protective capabilities to counter the injury that is incurred by IR in various organs (5)(6)(7)(8)(9)(10)(11)(12)(13), including the normal liver (14)(15)(16)(17). The protective mechanism of RIPC is highly complex (18)(19)(20)(21)(22) and involves the improvement of hepatic oxygenation (23), reduction of serum cytokine-induced neutrophil chemoattractant-1 levels (24), modulation of hepatic microcirculation (15) and activation of the soluble guanylate cyclase-cyclic guanosine monophosphate pathway (20), resulting in protective effects against IR injury.…”
Section: Introductionmentioning
confidence: 99%